Case Report: Resolution of high grade anal squamous intraepithelial lesion with antibiotics proposes a new role for syphilitic infection in potentiation of HPV-associated ASCC - Ranabhotu, A.; Habibian, N.; Patel, B.; Farrell, E.; Do, J.; Sedghi, S.; Sedghi, L. (Frontiers in Oncology, 2023)
Introduction: Human Papillomavirus (HPV) is the primary risk factor for the development of anal intraepithelial neoplasia (AIN) and is a leading risk factor for anogenital squamous cell carcinoma (ASCC). Despite common shared risk factors for both HPV and syphilis, co-infection is not well documented, and the role of syphilitic infection in HPV-associated AIN and ASCC potentiation is not defined. Case description/methods: A 72-year-old single male presented with complaints of mild rectal pain and intermittent rectal bleeding. A flexible sigmoidoscopy was performed, and a firm 4.5cm x 3cm perianal mass was detected and superficially biopsied. Pathology findings demonstrated evidence of a high grade squamous intraepithelial lesion (HGSIL, AIN II/III/AIS) with viral cytopathic effect, consistent with HPV infection. Much of the biopsied lesion showed acanthotic squamous mucosa with intraepithelial neutrophils and abundant submucosal plasma cells, suggesting possible syphilitic involvement. Subsequent immunohistochemical staining for p16 as a surrogate marker for HPV was positive, as was an immunohistochemical stain for spirochetes, supportive of co-infection with Treponema pallidum pallidum (T. pallidum), the causative agent in venereal syphilis. The patient was referred to an infectious disease specialist for syphilitic infection and was treated with penicillin with surprisingly complete resolution of the lesion. EUAs were performed 2-and 3-months following treatment without lesion recurrence. However, one year following diagnosis, a flexible sigmoidoscopy revealed a 5 mm recurrent HPVrelated low-grade AIN 1 lesion at the dentate line. Discussion: Resolution of the lesion by antibiotic treatment for syphilitic infection suggested that co-infection by T. pallidum may potentiate HPV-associated squamous cell carcinoma based on histological findings. Findings from this case, as well as a review of bacterial involvement and potentiation in various cancers, are reviewed here. Such findings offer new insight regarding the role of STI-associated bacteria and HPV co-infection in the establishment of AIN and may additionally propose new treatment modalities for ASCC.